(untitled) (Journal of Human Sciences, 2025)
In the Ottoman era, a type of castle became widespread, usually built inside cities, and on the sea coasts close to cities. They were Known as castles connected to the cities. The main goal of their establishment was to protect the rulers, their followers, and their soldiers from external dangers, in addition to be used an important means of eliminating strife and disturbances that might occur within the city. In addition to its function to repel enemy attacks coming from the sea or land if that happens, these are the motives for which most castles in Libya were built. Among these existing castles are Maple castle and Tokra castle, in addition to the rest of the vanished castles that were described by travelers in the cities of Benghazi, Derna, Al-Marg. In this study, we will discuss a new castle to added to the other castles which is called Marsa Lick castle.